Mannhemia haemolytica bacterial polypeptides and sequences, gene sequences and uses thereof. - Saad, Mohd Zamri; Mohd Yusoff, Md Sabri (2007)

(untitled)
The present invention provides a mannheimian bacterial polypeptide and includes polypeptide sequences, gene sequences encoding the polypeptide, vectors to contain the said sequences, and host cells transformed with the said vectors which include nucleotide sequences of the polypeptide sequences. The present invention 10 also provides antibodies directed against the polypeptides. Also provided in the present invention is the use of the polypeptide as a therapeutic agent for the prevention and treatment of mannheimian bacterial infections.